2007
DOI: 10.1097/qad.0b013e328011e691
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 protease and reverse transcriptase mutations for drug resistance surveillance

Abstract: This list, which should be updated regularly using the same or similar criteria, can be used for genotypic surveillance of transmitted HIV-1 drug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
289
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(303 citation statements)
references
References 35 publications
2
289
3
1
Order By: Relevance
“…In recent years, the transmitted resistance occurrence has been increasing due to scaled-up antiretroviral treatments. In Europe, North America, and Brazil, it has been reported that the prevalence of drug resistance ranges from 5-15% in newly diagnosed individuals (14). Because our untreated sequence data were collected from 1982 to 2005, it is possible that there are several transmitted drug resistant sequences in the untreated group that may affect both the sensitivity of our BVP algorithm and the power of our Bayesian model structure inference method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the transmitted resistance occurrence has been increasing due to scaled-up antiretroviral treatments. In Europe, North America, and Brazil, it has been reported that the prevalence of drug resistance ranges from 5-15% in newly diagnosed individuals (14). Because our untreated sequence data were collected from 1982 to 2005, it is possible that there are several transmitted drug resistant sequences in the untreated group that may affect both the sensitivity of our BVP algorithm and the power of our Bayesian model structure inference method.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HIV-1 drug resistance can be not only acquired (developing in a person receiving antiretroviral treatment) but also transmitted (occurring because a virus with drug-resistance mutations was transmitted to a drug-naive person) (14). In recent years, the transmitted resistance occurrence has been increasing due to scaled-up antiretroviral treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Due to rapid and error-prone viral replication, drug-resistant HIV-1 variants are inevitably selected during therapy with all currently available antiretroviral agents (3). Accumulation of mutations in the protease-encoding gene results in the emergence of multidrug-resistant (MDR) HIV-1 variants carrying a protease with an altered three-dimensional structure (4).…”
Section: H Uman Immunodeficiency Virus Type 1 (Hiv-1) Protease (Pr)mentioning
confidence: 99%
“…In Brazil, triple We have studied a group of HIV-1 perinatally infected children receiving prolonged antiretroviral treatment and we report in this paper the results concerning the drug resistance mutations profile observed in this group. These mutations were classified according to the current list of resistance mutations proposed by Shafer et al (2007).…”
Section: Introductionmentioning
confidence: 99%